Bibliometric Analysis of Revolutionizing Physical Activity: Challenges and Potentials of Emerging Technologies - Rahayu, Nur Indri; Muktiarni, M; Al Husaeni, Dwi Fitria; Ismail, Affero (International Journal of Research and Applied Technology (INJURATECH), 2023)
New technologies such as artificial intelligence (AI), virtual reality (VR), wearable devices, and digital applications are changing the way physical activity is understood, promoted, and practiced. This study was conducted with the aim of assessing the intellectual structure and research trends on the physical activity revolution, especially in analyzing the challenges and potentials of using technologies. The study analyzed publication trends, citation patterns, distribution geography, high-impact journals, and author collaboration analysis. Data were sourced from the Scopus database covering the time span of 2010 to 2024. Network visualization maps were used to reveal collaborative networks among researchers to identify subfields and emerging knowledge gaps. The results found that keywords such as “physical activity”, “health promotion”, and “sports” also indicate that health research has become very popular. Furthermore, the inclusion of modern technologies such as “artificial intelligence” and “virtual reality” show how health research has changed. These findings provide valuable insights into the evolution of research in this field, highlighting influential studies and emerging trends that shape the future of physical activity and health promotion. This analysis serves as a resource for researchers, policy makers, and practitioners to align their strategies with evidence-based practices and encourage interdisciplinary collaboration in leveraging technology to improve physical activity outcomes.